1967
DOI: 10.1111/j.1600-0609.1967.tb01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycythaemia Vera and Myelofibrosis

Abstract: Bone marrow biopsies were made in 63 patients with polycythaemia vera and in three patients with primary myelofibrosis having polycythaemic blood pictures. The histological findings in polycythaemia vera were classified as follows: normal bone marrow in 14, hyperplastic bone marrow in 17, hyperplastic bone marrow with increased reticulin fibers in 19, early myelofibrosis in 9 and advanced myelofibrosis in 4 patients. In 12 of the polycythaemic patients bone marrow biopsy was repeated after nine to 32 months. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1973
1973
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The main conclusion of the present study SPLEEN ASPIRATES IN POLYCYTHAEMIA VERA 61 is a negative one: myeloid metaplasia does not contribute to the splenomegaly of uncomplicated PV. Apparently this statement is at variance with the observations of Ikkala et al (1967), who found extramedullary haemopoiesis in 11 out of 17 spleen aspirates from cases of PV. However, this high figure is probably due to the fact that most patients in this series had reached an advanced stage of the disease, most of them already classified as cases of myelofibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…The main conclusion of the present study SPLEEN ASPIRATES IN POLYCYTHAEMIA VERA 61 is a negative one: myeloid metaplasia does not contribute to the splenomegaly of uncomplicated PV. Apparently this statement is at variance with the observations of Ikkala et al (1967), who found extramedullary haemopoiesis in 11 out of 17 spleen aspirates from cases of PV. However, this high figure is probably due to the fact that most patients in this series had reached an advanced stage of the disease, most of them already classified as cases of myelofibrosis.…”
Section: Discussionsupporting
confidence: 57%